The justice of God’s kingdom - Vorster, Jacobus M. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
This article explores the meaning of Jesus’s teaching in Matthew 6:33 from a systematic-theological perspective to gauge its implications for Christian moral agency in contemporary South Africa. The research question is: ‘What is the moral relevance of seeking God’s kingdom and his righteousness in South Africa today – a society plagued by economic inequality, moral decay, corruption, and pockets of hedonism?’ This question gives rise to the following sub-questions: Does Jesus teach us to withdraw from social challenges into an above-worldly sphere of pietism, seeking only a consoling spiritual relationship with God? Is the righteousness of the kingdom purely spiritual? Does it carry social implications? Can these implications be translated into social – even radical – social actions? How should Matthew 6:33 be understood and preached in present-day South Africa. The central-theoretical argument of the article is twofold: (1) the righteousness of the kingdom entails a sound relationship with God in Christ, which renews all other relationships of Christian believers; and (2) it requires their potent involvement in social justice. This research question and sub-questions will not be approached primarily from a biblical grammatical-historical perspective but rather from a systematic-theological perspective, with reference to biblical studies. Contribution: Firstly, this appraisal revisits the concept of the kingdom of God and then focuses on the idea of God’s righteousness and its social relevance, Christian moral agency, and an ecclesiology of justice. In conclusion, the discussion offers reflections on the relevance of Matthew 6:33 in the South African context today.